Deadly intent - Plante, Lynda La (London : Pocket Books, 2009)
Drug lord Alexander Fitzpatrick has not been seen in ten years, but a recent murder leads DI Anna Travis to suspect he may still be active
Investigating the killing of a former murder squad colleague whose death proves to be only one of many, Detective Anna Travis tracks down one the most ruthless drug traffickers in the western world
Keywords: Travis, Anna (Fictitious character) -- Fiction; Women detectives -- England -- Fiction; Murder -- Investigation -- Fiction